Research and residency match: a near-peer online webinar - Justin-Pierre Lorange,; Anne Xuan-Lan Nguyen,; Jobanpreet Dhillon,; Caroline Najjar, (Canadian Medical Education Journal, 2022)
Implication Statement: Medical students have a wide range of opinions and expectations about research and face many challenges when pursuing it. Online research webinars have the potential to teach medical students about the value of research for various competitive and non-competitive specialties, while also providing them with the opportunity to network with recent medical graduates. When hosted virtually, these events have the potential to reach medical student across multiple provinces and provide them with insight on the different facets of research.